2013
DOI: 10.1186/2192-1709-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of water, sediments, and biogeochemical compounds in salt marshes

Abstract: Tidal oscillations systematically flood salt marshes, transporting water, sediments, organic matter, and biogeochemical elements such as silica. Here we present a review of recent studies on these fluxes and their effects on both ecosystem functioning and morphological evolution of salt marshes. We reexamine a simplified model for the computation of water fluxes in salt marshes that captures the asymmetry in discharge between flood and ebb. We discuss the role of storm conditions on sediment fluxes both in tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 118 publications
(143 reference statements)
5
65
0
1
Order By: Relevance
“…Although there are no significant differences in the particle size, a tendency to an increase of soil OM in the LD sites with decrease in particle size was found, which agrees with Madkour and Mohamed (2008). Studies on fluxes of OM have focused on the entire estuarine system, including fluxes from the ocean and nearby fluvial watersheds (Fagherazzi et al, 2013). However, it is important to determine the mechanisms controlling fluxes and the nature of OM within the tidal basin following the results of Arenas and De la Lanza (1981 and 1983) on soil OM biodegradability in a nearby coastal lagoon.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although there are no significant differences in the particle size, a tendency to an increase of soil OM in the LD sites with decrease in particle size was found, which agrees with Madkour and Mohamed (2008). Studies on fluxes of OM have focused on the entire estuarine system, including fluxes from the ocean and nearby fluvial watersheds (Fagherazzi et al, 2013). However, it is important to determine the mechanisms controlling fluxes and the nature of OM within the tidal basin following the results of Arenas and De la Lanza (1981 and 1983) on soil OM biodegradability in a nearby coastal lagoon.…”
Section: Discussionsupporting
confidence: 69%
“…High concentrations occurred during biologically dominated phase. This is because the hydrological phase increases the bioturbation and the transportation of organic material from external sources as well as the removal and oxidation of OM within the sediments due to drying and cracking of the soil during dry season (Arenas and De la Lanza, 1981; Fagherazzi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm the findings by Davidson-Arnott et al (2002), who stated that not only a large input of SSC (by large river discharges) is required for large amounts of sediment deposition but also a low wave activity. Van der Wal and Pye (2004), Möller (2006), Fagherazzi et al (2007), Delgado et al (2013), andFagherazzi et al (2013) showed that wind wave related shear stress is decreased by vegetation and topographic irregularities. In our study, this effect was reflected in a decrease in observed sediment export from the Kleine Noordwaard study area under conditions of moderately north and easterly winds at low river discharges, since the tidal flats in the north and east of the Kleine Noordwaard area are characterised by a relatively irregular topography due to vegetated remnants of old embankments and polder drainage ditches.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner and Kjerfve (2006) / year at Bly Creek, South Carolina, during a 1-year study. In Atlantic coast marshes, a larger magnitude in fluxes may be due to increased frequency and intensity of large storms resulting in storm surges, which facilitate sediment deposition (Fagherazzi et al 2013b).…”
Section: Discussion Atmospheric and Tidal Controls On Sediment Transportmentioning
confidence: 99%
“…Tidal energy appeared to be driving the magnitude of the flux within the tidal channels in these salt marshes. In other marshes, storm-driven surge has accounted for a large percent of sediment fluxes over time (Cahoon et al 1996;Turner et al 2006;Fagherazzi et al 2013b). However, not all of our sites responded to tidal energy; the discrepancy is likely a result of the lower range of velocities observed in Seal Beach2.…”
Section: Discussion Atmospheric and Tidal Controls On Sediment Transportmentioning
confidence: 99%